HUBUNGAN KUALITAS PELAYANAN KARYAWAN RECEPTION FRONT OFFICE DEPARTMENT DENGAN KEPUASAN PELANGGAN GRAND ZURI HOTEL PADANG - Pratamy, Rahayu; Yuliana, Yuliana; abrian, youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of this study is: 1) Describe the service quality of receptionfront office employees, 2) Describe the customer satisfaction, and 3) Analyze therelationship between service quality reception front office employee and customersatisfaction Grand Zuri Hotel Padang.This research is correlational. The study population was all subscribersGrand Zuri Hotel Padang. A sample of 96 customers are taken incidentally. Datawas collected using a questionnaire that had been tested for validity andreliability. Furthermore, the data were analyzed by descriptive and correlationwith the help of computer program SPSS version 16 o'clock.The results showed that: 1) The quality of the reception service is locatedin both categories (45%), 2) Customer satisfaction is the category of satisfaction(44%), 3) There is a positive and significant relationship between service qualityand customer satisfaction with a reception with the value of r amounted to 0,438(0,000 sig) with the interpretation of the relationship is quite strong.